Comparative net energy ratio analysis of pellet produced from steam pretreated biomass from agricultural residues and energy crops. (July 2016) - Shahrukh, Hassan; Oyedun, Adetoyese Olajire; Kumar, Amit; Ghiasi, Bahman; Kumar, Linoj; Sokhansanj, Shahab
Abstract: A process model was developed to determine the net energy ratio (NER) for the production of pellets from steam pretreated agricultural residue (wheat straw) and energy crops (i.e., switchgrass in this case). The NER is a ratio of the net energy output to the total net energy input from non-renewable energy sources into a system. Scenarios were developed to measure the effects of temperature and level of steam pretreatment on the NER of steam pretreated wheat straw and switchgrass pellets. The NERs for the base case at 6 kg h −1 are 1.76 and 1.37 for steam-pretreated wheat straw and switchgrass-based pellets, respectively. The reason behind the difference is that more energy is required to dry switchgrass pellets than wheat straw pellets. The sensitivity analysis for the model shows that the optimum temperature for steam pretreatment is 160 °C with 50% pretreatment (i.e. 50 % steam treated material is blended with the raw biomass and then pelletised). The uncertainty results for NER for steam pretreated wheat straw and switch grass pellets are 1.62 ± 0.10 and 1.42 ± 0.11, respectively. Highlights: Research focused on change of NER with change in feedstock. NER falls significantly with increased pretreatment temperature. Energy for steam pretreatment reduces and energy for drying increases. NER for steam pretreatment can be improved by changing pretreatment level.